Horizontal and vertical polarization: Task-specific technological change in a multi-sector economy - Sang Yoon Lee; Yongseok Shin (Queen Mary University of London, School of Economics and Finance, 2019)
We construct a multi-layer model of skills, occupations, and sectors. Technological progress among middle-skill occupations raises the employment shares and relative wages of lower- and higher-skill occupations (horizontal polarization), and those of managers over workers (vertical polarization). Polarization is faster within sectors that rely more on middle-skill workers, endogenously boosting their TFP. This shrinks their employment and output shares (structural change) if sector outputs are complementary. We empirically validate our theoretical predictions, and show that task-specific technological progress - which was faster for routine-manual tasks and slower for interpersonal tasks - played a major role in transforming the U.S. economy since 1980.
Keywords: J24; J31; L16; O14; O33; 330; job polarization; structural change; wage inequality; Technischer Fortschritt; Humankapital; Beschäftigungseffekt; Industrieökonomik